Malignant Breast Lesion Detection with MRI and its Accuracy - Muhammad Wasif Iqbal, Moazem Ali, Rabia Ashraf, Amina Noor, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Using histology as the gold standard, this study aims to determine whether or not magnetic resonance spectroscopy can reliably diagnose malignant breast lesions. Study Design: Cross-sectional Place and Duration: Conducted at department of Radiology Central Park Medical College, Lahore. Duration was 6 months from October 2021 to March 2022. Methods: This research included 75 females. Malignancy-suspicious palpable lesions were included. Patients completed a consent form admitting the hazards before any data was gathered. The kinematics and morphology of dynamically enhanced magnetic resonance (MRS) images were studied. MRS's choline peak (Cho) was utilized to detect cancer. Single-voxel technique was employed to evaluate MRS' diagnostic accuracy in cancer. MRS and biopsies were compared. Data was analyzed using SPSS 24.0. Results: Malignant lesions were found in 65 (86.7%) of the patients by MRS, and in 58 (77.3%) of the cases according to the histological findings. Malignant lesions by MRS most frequently showed a ductal enhancement or a peripheral enhancement morphology. The results of MRS showed a 78% specificity, 85% accuracy, 90% sensitivity, 75% NPV, and 91% PPV. Conclusion: MRS must be employed because of its better specificity, sensitivity, and accuracy in characterizing breast lumps. MRS is a specific, sensitive, and effective diagnostic technique for breast cancer. Keywords: Accuracy, Magnetic resonance spectroscopy (MRS), Malignant breast lesion, Histopathology,